Clozapine-Induced Fatal Fulminant Hepatic Failure: A Case Report - Albert Chang; Darin S Krygier; Nazira Chatur; Eric M Yoshida (Canadian Journal of Gastroenterology)
Fulminant hepatic failure (FHF) refers to the rapid development of severe acute liver injury with impaired synthetic function and encephalopathy in a person who previously had a normal liver or had well-compensated liver disease. The potential causes of FHF are numerous, but viral or toxin-induced hepatitis are the most common. Clozapine-induced hepatotoxicity has rarely been reported in the literature, occurs via an unknown mechanism and results in liver biochemical abnormalities that are usually of no clinical significance. In approximately 30% to 50% of patients treated with clozapine, there is an asymptomatic rise in serum aminotransaminase levels; however, there are no current guidelines for routine monitoring of liver function tests and liver enzymes during its use. Fatal fulminant hepatitis has only been reported in three patients receiving clozapine. A case of fatal FHF that occurred in a schizophrenic woman who began clozapine therapy shortly before her illness developed is described.